Job Stress and Workload as Determinants of Employee Performance: Mediated by Job Satisfaction Evidence from UD. XYZ Kediri: Stres Kerja dan Beban Kerja sebagai Penentu Kinerja Karyawan: Dimediasi oleh Kepuasan Kerja Bukti dari UD. XYZ Kediri - Kukuh Harianto; Rike Kusuma Wardhani (Universitas Muhammadiyah Sidoarjo, 2026)
This study investigates how work stress, workload, and job satisfaction influence employee performance at UD XYZ is a trading-sector SME. Specifically, the study examines the mediating role of job satisfaction in the relationships between work stress, workload, and performance. A quantitative associative research design was employed with a population of 35 employees using saturated sampling. Data were collected via structured questionnaires and analyzed using SPSS 26, including validity and reliability testing, classical assumption testing, regression analysis, and path analysis. The results indicate that work stress significantly reduces job satisfaction and performance, while job satisfaction positively affects performance. Job satisfaction mediates the relationship between work stress and performance, serving as a psychological buffer that mitigates the effects of stress. In contrast, workload does not significantly influence job satisfaction or performance, nor does job satisfaction mediate the impact of workload. These findings imply that managing work stress and enhancing job satisfaction are crucial for sustaining employee performance in SMEs. However, the study is limited by its small sample size and focus on a single company. Therefore, caution should be exercised when generalizing the results, and opportunities exist for broader, multi-organizational research.